Multifunctional MeHA hydrogel for living materials delivery with enhanced cartilage regeneration - Chen, Qunchao; Bai, Lang; Wan, Guoyang; Hao, Yuefeng; Yang, Xing; Zhang, Hongtao (Frontiers in Bioengineering and Biotechnology, 2025)
Particulated juvenile articular cartilage (PJAC) has emerged as a promising living material for articular defect treatment. However, the fragile nature of PJAC hinders its wide clinical application. Here, inspired by the chemical composition and hierarchical structure of natural cartilage, we developed a novel hydrogel carrier system for PJAC delivery. Our carrier system, MeHA@J@DM, utilized methacrylated hyaluronic acid (MeHA) to incorporate PJAC and coated it with a polymerized mixture of dopamine methacrylamide (DMA) and 2-methylacryloyloxyethyl phosphorylcholine (MPC), forming an adhesive lubricant, p(DMA-MPC). MeHA@J@DM exhibited excellent performance for PJAC protection with enhanced cell viability, bioactivity, and lubrication properties. We evaluated the effectiveness of MeHA@J@DM in cartilage cell migration, where juvenile cartilage showed greater efficiency and remodeling abilities. In vivo rabbit cartilage defect models demonstrated superior cartilage regeneration with the MeHA@J@DM hydrogel. Our findings suggest that MeHA@J@DM has translational potential for PJAC implantation to enhance cartilage regeneration and benefit patients with articular cartilage lesions.